New Thiophene-Butanol Derivatives: Synthesis, Spectroscopic Characterization, DFT, Biological Activities and in Silico Study - Ustabas, Resat; Suleymanoglu, Nevin; Celik, Fatih; Guler, Halil Ibrahim; Bektas, Kadriye Inan; Direkel, Sahin; Unver, Yasemin (Pleiades Publishing Ltd, 2023)
In this study, 3-methyl/5-bromo/5-nitro-thiophene-2-carbaldehydes were reacted with 4-amino-1-propanol and thiophene derivatives including alcohole group (1-3) were obtained. The newly compounds (1-3) were characterized by FTIR and NMR methods. The optimized geometries, NMR-IR data and MEP map of compounds 1-3 were obtained at DFT/B3LYP/6-311++G(d,p) level. The leishmanicidal activity against Leishmania infantum promastigotes was determined in vitro by microdilution broth method for compounds 1-3. As a result, compounds 1-3 studied were effective against Leishmania specie, while compound 3 was found to be effective at very low concentrations. In addition, compounds 1-3 were tested for their antimicrobial activity. 8 different pathogenic microorganisms were selected for the antimicrobial activity test. The compounds 1-3 showed antimicrobial activities, but compound 3 demonstrated excellent antimicrobial activities against all the tested microorganisms. To examine possible interactions between synthesized compound 3 and target proteins was used by in silico analysis.
Keywords: Thiophene; Schiff Base; DFT Study; Antibacterial; Leishmanicidal Activity and in Silico Study